Regulation of gene expression by translation factor eIF5A: Hypusine-modified eIF5A enhances nonsense-mediated mRNA decay in human cells. Issue 2 (3rd July 2017) - Hoque, Mainul; Park, Ji Yeon; Chang, Yun-juan; Luchessi, Augusto D.; Cambiaghi, Tavane D.; Shamanna, Raghavendra; Hanauske-Abel, Hartmut M.; Holland, Bart; Pe'ery, Tsafi; Tian, Bin; Mathews, Michael B.
ABSTRACT: Nonsense-mediated mRNA decay (NMD) couples protein synthesis to mRNA turnover. It eliminates defective transcripts and controls the abundance of certain normal mRNAs. Our study establishes a connection between NMD and the translation factor eIF5A (eukaryotic initiation factor 5A) in human cells. eIF5A modulates the synthesis of groups of proteins (the eIF5A regulon), and undergoes a distinctive two-step post-translational modification (hypusination) catalyzed by deoxyhypusine synthase and deoxyhypusine hydroxylase. We show that expression of NMD-susceptible constructs was increased by depletion of the major eIF5A isoform, eIF5A1. NMD was also attenuated when hypusination was inhibited by RNA interference with either of the two eIF5A modifying enzymes, or by treatment with the drugs ciclopirox or deferiprone which inhibit deoxyhypusine hydroxylase. Transcriptome analysis by RNA-Seq identified human genes whose expression is coordinately regulated by eIF5A1, its modifying enzymes, and the pivotal NMD factor, Upf1. Transcripts encoding components of the translation system were highly represented, including some encoding ribosomal proteins controlled by alternative splicing coupled to NMD (AS-NMD). Our findings extend and strengthen the association of eIF5A with NMD, previously inferred in yeast, and show that hypusination is important for this function of human eIF5A. In addition, they advance drug-mediated NMD suppression as a therapeutic opportunity for nonsense-associated diseases. We propose that regulation of mRNA stability contributes to eIF5A's role in selective gene expression.